Raman amplification effects on stimulated Brillouin scattering threshold in multiwavelength Brillouin-Raman fiber laser - Abass A.K.; Al-Mansoori M.H.; Jamaludin M.Z.; Abdullah F.; Al-Mashhadani T.F. (2023)
We report experimental results demonstrating the stimulated Brillouin scattering threshold (SBSTH) features in multiwavelength Brillouin-Raman fiber laser against Raman pump power (RPP) variation. The reduction of SBSTH is attributed to the Raman amplification on each of oscillated Brillouin pump power (OBP) and generated Stokes signals. The saturation in SBSTH is owing to the RPP depletion, this saturation is coincides with the appearance of Raman peak gain. In addition, the red shift effect became significant at RPP beyond 650mW and led to degradation of the Raman amplification. This degradation appeared as an increase in SBS TH after the saturation region. Moreover, the Brillouin Stokes comb can be generated only at the saturation region of the Raman amplification between 350 to 600 mW of Raman pump. 2012 IEEE.